2024
DOI: 10.1101/2024.02.15.580379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The flow of reward information through neuronal ensembles in the accumbens

Benjamin Arroyo,
Enrique Hernandez-Lemus,
Ranier Gutierrez

Abstract: The flow of reward information through neuronal ensembles in the nucleus accumbens shell (NAcSh) and its influence on decision-making remain poorly understood. We investigated these questions by training rats in a self-guided probabilistic choice task while recording single-unit activity in the NAcSh. We found that rats dynamically adapted their choices based on an internal representation of reward likelihood. NAcSh neurons encoded multiple task variables, including choices, outcomes (reward/no reward), and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(296 reference statements)
0
2
0
Order By: Relevance
“…In an active decision-making behavioral context, we also observed that the rat's brain seems to follow a general brain-wave like activation pattern reflecting sensorimotor transformations from stimuli to decision-making (Arroyo et al, 2024;Laboratory et al, 2023). Specifically, the brain wave is triggered by sampling the stimuli that initially recruit a small number of neurons, but then more and more neurons take part in encoding choice, anticipation, and reward outcome, in which this wave dissipates.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In an active decision-making behavioral context, we also observed that the rat's brain seems to follow a general brain-wave like activation pattern reflecting sensorimotor transformations from stimuli to decision-making (Arroyo et al, 2024;Laboratory et al, 2023). Specifically, the brain wave is triggered by sampling the stimuli that initially recruit a small number of neurons, but then more and more neurons take part in encoding choice, anticipation, and reward outcome, in which this wave dissipates.…”
Section: Discussionmentioning
confidence: 62%
“…Specifically, the brain wave is triggered by sampling the stimuli that initially recruit a small number of neurons, but then more and more neurons take part in encoding choice, anticipation, and reward outcome, in which this wave dissipates. Impressively, this wavelike recruitment seems to be brain-wide and distributed phenomenon, as it has been reported that it occurs in parallel in multiple cortical and subcortical brain regions (Arroyo et al, 2024;Fonseca et al, 2018;Gutierrez et al, 2010;Laboratory et al, 2023;Musall et al, 2019;Steinmetz et al, 2019), substantiating its importance for active sensory processing and decision making. More importantly, our results demonstrate that aIC and the OFC are not passive primary or secondary sensory cortices, in agreement with previous observations (Fonseca et al, 2018;Gutierrez et al, 2010;Juen et al, 2024;Vincis et al, 2020).…”
Section: Discussionmentioning
confidence: 86%